Orexin-A inhibits fictive air breathing responses to respiratory stimuli in the bullfrog tadpole (Lithobates catesbeianus) - Fonseca, Elisa M. [UNESP]; Janes, Tara A.; Fournier, Stéphanie; Gargaglioni, Luciane H. [UNESP]; Kinkead, Richard (The Company of Biologists, 2021)
In pre-metamorphic tadpoles, the neural network generating lung ventilation is present but actively inhibited; the mechanisms leading to the onset of air breathing are not well understood. Orexin (ORX) is a hypothalamic neuropeptide that regulates several homeostatic functions, including breathing. While ORX has limited effects on breathing at rest, it potentiates reflexive responses to respiratory stimuli mainly via ORX receptor 1 (OX1R). Here, we tested the hypothesis that OX1Rs facilitate the expression of the motor command associated with air breathing in pre-metamorphic bullfrog tadpoles (Lithobates catesbeianus). To do so, we used an isolated diencephalic brainstem preparation to determine the contributions of OX1Rs to respiratory motor output during baseline breathing, hypercapnia and hypoxia. A selective OX1R antagonist (SB-334867; 5-25 µmol l-1) or agonist (ORX-A; 200 nmol l-1 to 1 µmol l-1) was added to the superfusion media. Experiments were performed under basal conditions (media equilibrated with 98.2% O2 and 1.8% CO2), hypercapnia (5% CO2) or hypoxia (5-7% O2). Under resting conditions gill, but not lung, motor output was enhanced by the OX1R antagonist and ORX-A. Hypercapnia alone did not stimulate respiratory motor output, but its combination with SB-334867 increased lung burst frequency and amplitude, lung burst episodes, and the number of bursts per episode. Hypoxia alone increased lung burst frequency and its combination with SB-334867 enhanced this effect. Inactivation of OX1Rs during hypoxia also increased gill burst amplitude, but not frequency. In contrast with our initial hypothesis, we conclude that ORX neurons provide inhibitory modulation of the CO2 and O2 chemoreflexes in pre-metamorphic tadpoles.
Keywords: Chemoreception; Hypercapnia; Hypoxia; Orexin; Pre-metamorphic bullfrog tadpole; Respiratory control